Thrombopoietin receptor agonists for the treatment of primary immune thrombocytopenia: a meta-analysis and systematic review - Birocchi, Simone; Podda, Gian Marco; Manzoni, Marco; Casazza, Giovanni; Cattaneo, Marco (Platelets (Edinburgh), 2021)
Previous meta-analyses reported discordant results on the efficacy and safety of thrombopoietin receptor agonists (TPO-RA) as second-line treatment in patients with immune thrombocytopenia (ITP). We conducted a meta-analysis of primary ITP treatment with the TPO-RA Romiplostim, Eltrombopag and Avatrombopag, including additional studies and relevant endpoints. We searched MEDLINE, EMBASE and CENTRAL for randomized clinical trials (RCTs) and cohort studies on TPO-RA in ITP published until December 31, 2018. The primary endpoints were: risk ratio (RR) of treatment failure and bleeding of WHO grade ≥2; rate of remission after discontinuation of treatment. The principal safety outcome was RR and incidence of thrombotic events and liver damage. From 1044 identified records we selected 16 RCTs and 19 cohort studies. RCTs included 909 patients assigned to TPO-RA and 427 to the control arm. Treatment failure was observed in 21% TPO-RA-treated patients and 47% control arm patients (RR = 0.42, 95% CI 0.33-0.53) in RCTs during a median follow-up of 13 weeks, and in 29% TPO-RA-treated patients in cohort studies, during a median follow-up of 69 weeks. The incidence of remission after TPO discontinuation was 18% (5-36%). RR of WHO grade ≥2 bleeding was 0.58 (0.38-0.86) in TPO-RA-treated patients, compared to control arm patients. Adverse events were rare and not significantly different in the two groups of patients. All-cause mortality was significantly lower with TPO-RA (RR 0.21, 95% CI, 0.06-0.68). In conclusion, TPO-RA are effective and safe in patients with ITP, even in the long term.